METHODS FOR IMPROVING THE METHODOLOGY OF DEVELOPING STUDENTS' COMPETENCE THROUGH TEACHING ENGINEERING GRAPHICS - Begijonov Makhmudbek Sharibbek ugli (Bright Mind Publishing, 2025)
This research aims to improve the methodology for developing the project-technological competence of future engineers through the teaching of engineering and computer graphics. The rapid advancement of technology and the increasing complexity of engineering tasks necessitate innovative approaches to education. By integrating modern pedagogical strategies and digital tools into the curriculum, this study strives to enhance students' ability to effectively design, analyze, and implement engineering solutions. A mixed methodological approach was employed, encompassing an analysis of current teaching practices, experimental application of innovative methods, and assessment of student outcomes. The results demonstrate that the integration of computer modeling, interactive design tasks, and collaborative projects significantly enhances the project-technological competence of engineering students. These findings serve as a foundation for developing a more effective teaching methodology aimed at adapting educational practices to industry needs and technological advancements.
Keywords: Engineering graphics, Modern teaching methods, CAD programs, 3D modeling, Project-based learning, Interactive simulation, Students, Control group, Experimental group, Practical skills, Creativity, Teamwork, Innovative solutions, Teaching effectiveness, Educational technologies, Theoretical knowledge.